Integrating cultural elements of coastal communities in Ajuy, Iloilo as context in the development of learning modules for Grade 7 and grade 8 patterns and algebra of the K to 12 curriculum - Gancia, Ryan Cyril B (Iloilo University of the Philippines Visayas, 2019)
IN the Philippine setting, Mathematics is conventionally taught as a culturally-free discipline which usually leads to concepts irrelevants to learner's experiences. As a result, learners find it complex to create new academic mathematical knowledge and connect it with real-world. Thus, this paper is advanced to explore and investigate the ethnomathematics present in the culture of coastal communities of Ajuy, Iloilo, Philippines and develop learning modules on Patterns and Algebra for K to 12 Grades 7 and 8 Mathematics Curriculum. Through community immersion, the researcher explored the community funds of knowledge by interviewing community members and observing existing elements and practices in their environment. This study was anchored on the Theory of Social Constructivism and employed the CoLab (Community as Laboratory) Model where identified ethnomathematical elements found in the community were used to develop contextualized and culturally-relevant learning materials. These integrated concepts involved in activities and practices of the community such as the different fishing methods and materials, modes of travelling, boat design and framework,livelihood, local landmarks, and other objects similar to learners living in the community. Field testing was conducted to determine the cognitive and affective impacts of the contextualized learning modules in the learners through assessment test and ATMS questionnaire. Results reported that ethnomathematics related to Patterns and Algebra was found to be integrated in the activities of Punta Buri community. The learners had apprehensions towards the use contextualized learning modules but these enhanced their recognition of the relevance ofmathematics in their lives. The integration of mathematical concepts in familiar contexts enabled learners to be connected with the learning module. The developed modules are provided in this paper although these still need improvement so that it will serve as materials for individual learning. However, they may be utilized as substitute to the learning materials available for the learners.
Special Problem (MEd - Math) -- Iloilo : University of the Philippines Visayas, September 2019.